(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Multi-Drug resistant (MDR) Pseudomonas aeruginosa is the most common cause of of nosocomial infections, several virulence factors, including exoenzymes, exotoxins, and biofilm formation used by the organism to establish its pathogenicity. Aim of the work: To evaluate the distribution of different virulence genes and biofilm formation among MDR Pseudomonas aeruginosa isolated from different clinical microbiological samples. Patients and methods: A total of 117 Multi-Drug resistant Pseudomonas aeruginosa isolates were screened for the presence of eight virulence factors by using conventional PCR and for biofilm formation using colourimetric microtitre method. Results: among MDR Pseudomonas Aeroginosa AprA gene was found in 53% isolates, the same percentage was recorded in Exo S gene. ExoU, ToxA, PlcN genes were recorded to present in 59.8%, 97.4% and 8.5% respectively. However, PlcH gene was found in 36.8% isolates and LasB in 47.9% of isolates. 113 isolates were biofilm producers, 69 isolates were strong biofilm producers, 34 isolates were moderate biofilm producers and 10 isolates were weak biofilm producers. Also we recorded that 29(25%) isolates were positive to more than 6 genes. Regarding genotypic pattern of biofilm producers in MDR Pseudomonas aueroginosa isolates, AprA gene was detected among 59(52.2%) isolates, ExoU, ExoS, AlgD genes were recorded to present in 66(58.4%), 61(53.9%) and 108( 95.6%) isolates respectively. Conclusion: AlgD, ToxA and ExoU genes were the most predominant among MDR p.aeuroginosa isolates. Moreover, they recorded the highest percentage among biofilm producer isolates. Antibiotic resistance against pefloxacin, rifampicin, minocyclin, gentamicin and aztereonam were high, while resistance against tigecyclin and colistin were very low.